Breakdown of a geographic cline explains high performance of introduced populations of a weedy invader. (11th September 2017) - Endriss, Stacy B.; Alba, Christina; Norton, Andrew P.; Pyšek, Petr; Hufbauer, Ruth A.
Abstract: What drives the evolution of increased growth and fecundity in plants introduced to a novel range is not well understood. We investigate between‐range differences in performance for Verbascum thapsus, a weedy invader known to grow larger in its introduced than native range. Specifically, we question whether adaptation to herbivory or climate best explains increased performance of introduced populations. We grew 14 native and 22 introduced populations of V. thapsus in two common garden locations: near Prague, Czech Republic (native range) and in Colorado, USA (introduced range). By removing herbivores from half of the plants within each garden we tested the prediction of the evolution of increased competitive ability (EICA) hypothesis: increased performance is driven by an evolutionary shift of resources away from defence against herbivory towards growth and reproduction. We then investigated whether genetically based clines in performance are expressed along climate gradients within both the native and introduced ranges. On average, seeds produce larger rosettes when collected from the introduced vs. native range. While this evolution of increased growth in introduced populations in part matches the prediction of EICA, climate, not herbivory, best explains this between‐range difference. Specifically, seeds collected from the native range produce smaller rosettes as the climate of origin becomes cooler and drier, while there is no cline in performance in rosettes grown from seed collected from the introduced range, which are large regardless of climate of origin. Thus, a climate‐based cline within the native range best explains lower average performance of native compared to introduced populations. Synthesis . The breakdown in a potentially adaptive cline emphasizes the need to more closely investigate the evolutionary processes that shape geographic structuring (or its absence) within the introduced range. In addition, EICA is not universally applicable to all invasion scenarios, and our findings underscore the importance of testing the underlying assumptions alongside the predictions of this hypothesis. Abstract : The breakdown of a cline in performance along climate gradients, not adaptation to herbivory, best explains high performance of introduced as compared to native populations of a weedy invader. Our findings emphasize the need to: (1) test the underlying assumptions alongside the predictions of EICA, and (2) further investigate processes shaping geographic structuring (or its absence) within the introduced range.